Fe(ii)-Complexation of tripodal hexapeptide ligands with three bidentate triazolylpyridines: induction of metal-centred chirality by peptide macrocyclization. Issue 40 (27th September 2017) - Kobayashi, Yuka; Kameda, Tomoshi; Hoshino, Masaru; Fujii, Nobutaka; Ohno, Hiroaki; Oishi, Shinya
Abstract : Cyclic and open-chain hexapeptides with three common triazolyl-pyridine residues afforded two Fe(ii ) complexes with distinct metal-centred chirality. Abstract : Fe(ii )-Coordinating peptides, having three bidentate 2-(1, 2, 3-triazol-4-yl)pyridine moieties at their side-chains, were designed based on the naturally occurring siderophore structures. The C 3 -symmetric macrocyclic peptide and an open-chain congener with the same sequence formed Fe(ii )–peptide complexes with opposite metal-centred chiralities.